URGENSI ILMU AL-JARH WA AL-TA'DIL DI ZAMAN KONTEMPORER - Rohimah Rohimah; Yeni Anggraeni; Dina Aljahra Aini; Muhammad Alfan Fadilah (DIRAYAH : Jurnal Ilmu Hadis, 2024)
Particularly present day, science al jarh wa al ta'dil a crucial field in study of hadish. This science determines whether hadiths can be accepted or rejected source islamic teaching by evaluating and confirming the veracity and integrity of hadith narrators. The need aljarh wa al ta'dil's science is growing in order to preserve the integrity and veracity of the Prophet Muhammad's sunnah in light of the dissemination of erroneous or weakened hadiths via a variety of media platforms. This study looks at the relevance and urgency of al jarh wa al ta'dil science in modern world and how it affects attempts to uphold the integrity of Islamic teachings and offer answers derived from reliable sources. This study discovered through a thorough analysis of the literature that it is crucial for scientists, scholars, and Muslims in general to master and apply aljarh wa al ta'dil's science is in order to distinguish between authentic and fake hadiths and to offer guidance that is in line with the Prophet Muhammad's teachings. Thus, having this information is essential to upholding the integrity of Islamic teachings and providing genuine, trustworthy answers to today's problems.